P099 Risk of obstructive sleep apnoea in patients with rheumatic disease: a prospective cohort study. (26th April 2021) - Ng, Wan Lin; Kamarudin, Nurasyikin; Anjum, Aqeel; Devlin, Joe; O'Brien, Aidan; Fraser, Alexander
Abstract: Background/Aims   Sleep plays an important component in our lives and sleep abnormalities have been known to be linked with various rheumatic conditions. Obstructive sleep apnoea (OSA) could potentially affect the severity of rheumatic symptoms such as pain, fatigue and also influence the disease activity. This study aims to evaluate the risk of OSA in patients with rheumatic diseases in an Irish cohort. Methods   Patients with a diagnosis of a rheumatic disease were recruited from rheumatology outpatients. These patients were asked to complete the Berlin Sleep Questionnaire (BSQ) to evaluate their level of risk for OSA. The Health Assessment Questionnaire (HAQ), Patient Global Assessment (PtGA) and the Physician Global Assessment (PhGA) were also completed. Results   These patients were asked to complete the Berlin Sleep Questionnaire (BSQ) to evaluate their level of risk for OSA. The Health Assessment Questionnaire (HAQ), Patient Global Assessment (PtGA) and the Physician Global Assessment (PhGA) 111 patients were recruited. Mean age was 52 years and 22 (19.8%) were males. The most common diagnosis in our cohort was rheumatoid arthritis 54 (45.4%), followed by spondyloarthritis 12 (10.1%), psoriatic arthritis 11 (9.2%), systemic lupus erythematosus 9 (7.6%), Behçet's disease 7 (5.9%), scleroderma 6 (5.0%) and others 20 (16.8%); with 8 patients having two diagnoses. Our cohort also completed the HAQ which demonstrated 98 (88.3%) having mild to moderate disability and 13 (11.7%) having moderate to severe disability. 39 out of 111 were noted to have a high risk for OSA based on the BSQ. In the high risk cohort, the mean PtGA score was 46.5 while PhGA score was 30.3, compared to the low risk cohort which was 36.7 for PtGA and 24.9 for PhGA. 33 (84.6%) patients in the high risk cohort had mild to moderate disability and 6 (15.4%) had moderate to severe disability as compared to 64 (88.9%) with mild to moderate disability and 8 (11.1%) with moderate to severe disability in the low risk cohort.were also completed. Conclusion   This is the first prospective study in Ireland to evaluate the risk of OSA in patients with rheumatic diseases. 35.1% from our cohort were found to be at high risk for OSA and are due to undergo overnight pulse oximetry and polysomnography to objectively assess the presence or absence of OSA. The disease activity reported by both patient and physician along with the level of disability were greater in the high risk cohort. This suggests that OSA increases the likelihood of exacerbating rheumatic activities. Disclosure   W. Ng: None. N. Kamarudin: None. A. Anjum: None. J. Devlin: None. A. O'Brien: None. A. Fraser: None.